ENHANCING READING ABILITY OF SMP BUDI DHARMA DUMAI STUDENTS THROUGH ICRS BASED ON CEFR - Army, Adinda Mutiara; Erni, Erni; Azhar, Fadly (Universitas PGRI Sumatera Barat, 2025)
This quantitative pre-experimental research was undertaken to investigate the pedagogical efficacy of the CEFR-aligned Inquiry Complexity Reading Strategy (ICRS) model in enhancing the reading proficiency of second-year students (N=26) at SMP Budi Dharma Dumai. Rooted in the principles of Inquiry-Based Learning and Connectivism, the ICRS model was implemented to actively foster critical and creative reading ability through collaboration. Data collected via a One Group Pretest-Posttest design were analyzed using a paired-samples t-test. The empirical results demonstrated a statistically significant enhancement in reading ability, evidenced by the substantial increase in the mean score from 58.85 (Fair) to 82.88 (Excellent). The t-test confirmed this significant difference (p < 0.05), further supported by a very large effect magnitude (Cohen’s d = -2.061). These findings lead to the conclusion that the CEFR-based ICRS model is highly effective in improving overall reading proficiency, successfully reducing the achievement gap, and supporting the differentiated learning goals of the Merdeka Curriculum in the English as a Foreign Language (EFL) context.